The exhortations of George Trapezuntios and Cardinal Bessarion against the Ottomans :|Identities and representations - Avila, Agustin Rafael. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
During the last years of the Byzantine Empire and after its collapse, some Greek intellectuals became deeply concerned with the international affairs and the fate of their nation, and assumed the task of writing crusading exhortations against the Ottomans to the leaders of Western Europe. This research focuses particularly on the crusading literature produced by George Trapezuntios and cardinal Bessarion. Whereas the latter was educated in Constantinople, the former was born and grew up on the island of Crete, which was under Venetian rule but maintained a firm Greek cultural identity. Thus, the initial education of Trapezuntios and Bessarion was in accordance with the traditional Byzantine curriculum. However, well before the fall of Constantinople, both of them migrated to Italy, where they engaged with the study of Latin culture. Their exhortations against the Ottomans, which were written in a learned Latin, exhibit a singular amalgamation of both traditions and are a valuable testimony of their life and thoughts. The first part of this study consists of the translation, contextualization and commentary of these orations. The second part is a comparative analysis of the texts focused on the matter of Byzantine identity, the representation of the Ottomans and the way in which the authors conceived the course of history.